Critical Systems Heuristics for Sustainable Management of Iran's Water-Energy-Food Nexus - Samira Ebrahimi; Mohammad Reza Fathi; Meisam Shahbazi (Journal of Systems Thinking in Practice, 2025)
The Water-Energy-Food (WEF) nexus represents a critical framework for sustainable development, ensuring human survival and ecological balance amidst increasing resource pressures from population growth, urbanisation, climate change, and economic development. While many models aim to address this nexus, they often focus narrowly on specific sectors rather than adopting a comprehensive, holistic perspective. This study employs Critical Systems Heuristics (CSH), a reflective and emancipatory approach, to examine the systemic challenges and underlying assumptions within the WEF nexus in Iran. The research involved 25 experts from diverse fields—energy (n=6), water (n=5), food (n=4), academia (n=6), and systems (n=4)—selected through purposive sampling to ensure diverse perspectives. Using boundary critique, the study examines current realities (“is” states) and ideal visions (“ought” states) through twelve boundary questions that assess sources of motivation, power, knowledge, and legitimacy. Findings reveal fragmented decision-making structures, short-term planning approaches, and insufficient interdisciplinary collaboration as significant obstacles to sustainable resource management. While decision-making authority is concentrated in isolated governmental sectors, the study highlights the need for integrated management frameworks that align with long-term sustainability goals, emphasising public welfare, environmental preservation, and inclusivity. Additionally, the research uncovers a gap in leveraging relevant expertise, with reliance on politically influenced appointments over merit-based inclusions. The study advocates for systemic reforms, including interdisciplinary stakeholder engagement, the establishment of a unified governance body for the WEF nexus, legislative adaptations, and the integration of renewable energy and sustainable agricultural practices. These strategies aim to shift decision-making from short-term political gains to fostering resilience and equity for current and future generations. By addressing the socio-political, technical, and ecological dimensions of the WEF nexus, this research provides policymakers, stakeholders, and researchers with actionable insights, contributing to a more integrated and sustainable approach to resource management in Iran.